Temperature control in a solar collector field using Filtered Dynamic Matrix Control. (May 2016) - Lima, Daniel Martins; Normey-Rico, Julio Elias; Santos, Tito Luís Maia
Abstract: This paper presents the output temperature control of a solar collector field of a desalinization plant using the Filtered Dynamic Matrix Control (FDMC). The FDMC is a modified controller based on the Dynamic Matrix Control (DMC), a predictive control strategy widely used in industry. In the FDMC, a filter is used in the prediction error, which allows the modification of the robustness and disturbance rejection characteristics of the original algorithm. The implementation and tuning of the FDMC are simple and maintain the advantages of DMC. Several simulation results using a validated model of the solar plant are presented considering different scenarios. The results are also compared to nonlinear control techniques, showing that FDMC, if properly tuned, can yield similar results to more complex control algorithms. Abstract : Highlights: The DMC algorithm is interpreted through a dead-time-compensation scheme. A modification is proposed to improve robustness and disturbance rejection of DMC. The proposed controller is applied to a solar collector field in a water desanilization plant. Comparisons are made of the proposed controller and nonlinear control techniques. Experimental disturbance data is used to validate the controller.